Numerical Study of Rock Blasting; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Stefanov Yu. P.; Bakeev R. A.; Yudin A. S. Artem Sergeevich; Kuznetsova N. S. Nataliya Sergeevna (2015, 2015)
Title screen